Bioleaching of Molybdenum by Two New Thermophilic Strains Isolated and Characterized - Mahshid Roshani; Seyed Abbas Shojaosadati; Seyed Jaber Safdari; Ebrahim Vasheghani-Farahani; Kazem Mirjalili; Zahra Manafi (Iranian Journal of Chemistry & Chemical Engineering, 2017)
This study involves the isolation and characterization of a bacterial strain capable of bioleaching molybdenum ore. Bacterial growth was observed when rock sample was incubated in 9K at 70 ºC. The isolates were identified as extremely acidophilic, thermophilic and chemolithotroph archaebacteria. Following PCR amplification of the 16S rDNA of the isolated strain, the sequencing of this region and comparison with the Gen-Bank database identified the strains as Acidianus ambivalens and Sulfolobus solfataricus. An experimental design was carried out to optimize bioleaching of molybdenum by these bacteria. Factors of pulp density, initial pH, the concentration of Fe3+ and the ratio of two bacteria are the variables and molybdenum and uranium recoveries were selected as responses. Bioleaching was carried out using molybdenum ore and pulp density of 4%, initial pH of 1.5, Fe3+ concentration of 11.5 g/L and Sulfolobus solfataricus  to Acidianus ambivalens ratio of 2.0 were selected as optimum conditions. Molybdenum and uranium recoveries were 43.2% and 79.1% respectively.